Оценка эпидемиологии кариеса и его осложнений у лиц старшего возраста (Эндодонтия Today, 2020)
Group of 100 dental patients aged from 70 to 86 yrs (40 female and 60 male) medical and dental care in the hospital affiliated to Board of Affairs of the President of Russian Federation was checked medically and dentally. Cardiovascular diseases and endocrine pathology was revised as the medical history. Dental inspection involved dental clinical and radiological assessment with recording the status of each tooth in accordance with international epidemiological conventions. Teeth with endodontic pathology (primary or in root-canal treated teeth) were recorded particular. In mean number of DMFT was over 19 in studied group. Dental Treatment degree was higher than 80% (based on «decayed teeth/filled teeth» ratio) and higher than 90% (based on «decayed teeth/missing+filled teeth» ratio). The occurrence of Filled Teeth was dominating over Missed Teeth. The occurrence of Endodonticly compromised teeth exceeded 48% in the mean number of DFT. Positive correlation between mean number of DMFT and «decayed teeth/filled teeth» ratio suggests the need of the in-time dental treatment of incipient decay lesions in elderly patients. Epidemiological data of the study suggest the importance of developing special oral health inspection and treatment protocols for elderly patients.